Bcl-3 regulates the function of Th17 cells through raptor mediated glycolysis metabolism - Liu, Hui; Zeng, Lin; Yang, Yang; Huang, Zhen; Guo, Chunlei; Huang, Liwenhui; Niu, Xinqing; Zhang, Chenguang; Wang, Hui (Frontiers in Immunology, 2022)
Bcl-3 is an atypical IκB family member that regulates transcription in the nucleus by binding to the p50/p52 homologous dimer subunit. Although various studies illustrate the important role of Bcl-3 in physiological function, its role in metabolism is still unclear. We found that Bcl-3 has a metabolic regulatory effect of Bcl-3 on autoimmunity. Bcl-3-depleted mice are unable to develop experimental autoimmune encephalomyelitis. The disease resistance was linked to an increase in lactate levels in Th17 cells, and lactate could alleviate EAE development in WT mice. Bcl-3 deficient mice had more differentiated Th17 cells and an increased extracellular acidification rate in these cells. Concurrently, their ultimate respiration rate and respiratory reserve capacity were significantly lower than wild-type mice. However, adding GNE-140 (LADH inhibitor) to Bcl-3-deficient Th17 cells could reverse the phenomenon, and lactate supplementation could increase the glycolysis metabolism of Th17 cells in WT mice. Mechanically, Bcl-3 could interact with Raptor through ANK and RNC domains. Therefore, Bcl-3 regulates Th17 pathogenicity by promoting Raptor mediated energy metabolism, revealing a novel regulation of adaptive immunity.